PENGARUH PEMBERIAN AIR KELAPA HIJAU TERHADAP TINGKAT NYERI DISMENORE PADA REMAJA PUTRI POSYANDU REMAJA SEHATI KECAMATAN SAWANGAN TAHUN 2023 - Wahyuni, Diana Rifka Yulia (Journal of Midwifery Tiara Bunda, 2023)
Background: Menstruation is periodic bleeding from the uterus which starts about 14 days after ovulation periodically due to the detachment of the uterine endometrial lining. The incidence of dysmenorrhea in West Java was quite high, the results of the study found that 54.9% of women experienced dysmenorrhea, consisting of 24.5% experiencing mild dysmenorrhea, 21.28% experiencing moderate dysmenorrhea and 9.36% experiencing severe dysmenorrhea. One of the treatment for menstrual pain with other non-pharmacological therapies can be used by consuming coconut water. Objective: This study aimed to determine the effect of giving green coconut water on dysmenorrhea pain among adolescent girls in Berekah village, Sukabumi district in 2021. Methodology: This study was a Quasi Experiment using a pretest-posttest design with a control group. The sampling technique used was purposive sampling which consisted of 30 adolescent girls who experienced dysmenorrhea every menstruation. The data were analyzed using the Paired T-Test to determine the difference in scores in one group and the Independent T-Test to determine the difference in scores between groups. Results: The results showed that there was a significant difference in the dysmenorrhea pain scale before and after being given green coconut water (p <0.05). Conclusion: Green coconut water has an effect on reducing the dysmenorrhea pain scale among adolescent girls. Suggestion: It is hoped that green coconut water can be applied thoroughly as a traditional treatment in dealing with dysmenorrhea pain in adolescent girls.